Stakeholder engagement for circular economy in the built environment: a comparative study of London and São Paulo - Loviscek, Vittoria (2023)
The Built Environment sector's extensive resource depletion, waste generation, and greenhouse gas emissions underscore the need for collaboration among stakeholders. This collaboration is vital for finding solutions that promote economic growth, harness the potential of circular productive systems, and extract value from existing materials and resources. This study investigates the relationships among stakeholders of the Built Environment supply chain to understand their motivations, engagement strategies, and the resulting actions to develop and implement practices of circular economy at all stages of the loop of the construction supply chain. The investigation consists of a comparative casestudy between London and São Paulo. Stakeholders of the whole supply chain are included in the research considering the private sector, the public sector and the third sector. Stakeholder Theory is integrated into the literature of Circular Economy to employ the ReSolve framework for the developing and implementing circular business models (CBM) in this industry. The research addressed the following question: how do stakeholders of the value chain and value network interact, and what engagement strategies are involved in the process of development and implementation of circular economy practices in the loop of the built environment? The study is meant to fill a research gap by providing a holistic picture and understanding of the ongoing relationships and strategies for CBM development. By considering (1) types of stakeholders, (2) motivations of stakeholders, (3) stakeholder engagement strategies, (4) stakeholders’ action integrated with the ReSolve Framework, and (5) CBMs of the Built Environment supply chain, this investigation provides a clear focus for decision-making for all the sectors involved and clear directives for further investigations. The originality lies in its contextual characteristic of comparing London and São Paulo. The main results show that in a context with a strong policy framework, managers mostly focus on raising awareness and providing educational training, while in a context with a weaker policy framework, managers pressure the supply chain to adapts to environmental requirements by adopting certifications and green labels. The research also provides a theoretical model by understanding the integration of the ReSolve Framework with stakeholder management strategies. It concludes by providing theoretical contributions and managerial best practices and insights.